Current index sets for measuring public sector innovation in Vietnam: Realities and requirements - PHẠM THỊ CHI; HOÀNG ANH (Political Theory Journal, 2026)
The article focuses on reviewing and analyzing the system of innovation measurement index sets currently applied in Vietnam, including international and domestic indices. Based on an analysis of the structure, methodology, and reflective scope of these index sets, the article points out theoretical and practical gaps in measuring current public sector innovation. On that basis, it proposes principled requirements for building a specialized index set, contributing to promoting modern, enabling governance capacity in the context of national digital transformation.